Relationship between obesity and frailty in an old age population of Sindh, Pakistan - Kainat Faizan; Aadil Ameer Ali (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2021)
Objective: To identify the Relationship between Obesity and Frailty in an old age Population of Sindh, Pakistan.  Methodology: A cross sectional survey was conducted in many different hospitals of Karachi, Pakistan in December 2017. A self-constructed questionnaire was used which includes which includes the demographics, health status of patients, the Body Mass Index (BMI) and to analyze the data acquired, we used SPSS version 23. Results: 89.1% (n=339) of the participants belong to age group of 60-65 years and 57.3% (n=216) were male. Moreover, the Majority (n=183, 78.8%) of the participants reported with poor health status. After checking the level of Frailty among the participants, (n=218, 58%) of the participants were found to be frail. Conclusion: This Study concluded that there is significant impact of obesity on Frailty, because as the people ages the level of calcium and vitamin D in the bones decreases, bone become fragile and cannot support the increased weight of an individual which leads to weakness and susceptibility to disease.